Intra-abdominal removal of a displaced hip prosthesis. (2015) - Morrison, Rory; Adegbola, Sam; Bhattacharya, Vish
Highlights: Laparotomy and removal of the prosthetic head is possible and preferred in some cases where further damage to the iliac bone may be caused by removal via a usual exterior approach. A sound planning strategy should be made with CT, ultrasound or laparoscopy. Retroperitoneal surgery has been described but intraperitoneal surgery is also a possibility. A good knowledge of pelvic organs and vessels is essential. Combined surgery with vascular surgeons is recommended. Abstract: INTRODUCTION: Intra-pelvic displacement of hip prostheses is an uncommon complication following arthroplasty surgery but can have significant detrimental effects on the patient. We present a case of a displaced hip prosthesis into the pelvic cavity and highlight the importance of pre-operative planning and investigation as well as choosing a suitable surgical approach. PRESENTATION OF CASE: A 69 year old lady with developmental dysplasia of the hips was found to have displacement of her prosthesis into the pelvis on day three following complex uncemented total hip replacement. A subsequent combined procedure between vascular and orthopaedic surgeons was carried out, including access via a laparotomy incision to allow vision and control of the iliac vessels before removal of the prosthesis. The hip was reconstructed during the same operation using a cup cage construct, reinforced with plate fixation of the posterior column of the pelvis. DISCUSSION: Intra-pelvic displacement of hip prostheses is rare and morbidity and mortality can be significant. Pre-operative imaging modalities such as CT scanning should be used to carefully delineate the anatomy. A retro-peritoneal approach has been reported, but we used a trans-abdominal approach in this case to permit greater vision and control of pelvic structures due to the significant medial displacement of the prosthesis. CONCLUSION: Intra-abdominal removal of a displaced hip prosthesis is rarely performed but allows for visualisation and careful control of the pelvic structures without damaging further the pelvic wall. We recommend this approach should be performed in conjunction with a vascular surgeon.